2015
DOI: 10.1586/17474124.2015.1042861
|View full text |Cite
|
Sign up to set email alerts
|

Extra-esophageal gastroesophageal reflux disease and asthma: understanding this interplay

Abstract: Gastroesophageal reflux disease (GERD) is a condition that develops when there is reflux of stomach contents, which typically manifests as heartburn and regurgitation. These esophageal symptoms are well recognized; however, there are extra-esophageal manifestations of GERD, which include asthma, chronic cough, laryngitis and sinusitis. With the rising incidence of asthma, there is increasing interest in identifying how GERD impacts asthma development and therapy. Due to the poor sensitivity of endoscopy and pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 121 publications
(85 reference statements)
0
42
0
4
Order By: Relevance
“…Research suggests that GERS may lead to or exacerbate asthma and be associated with poor asthma control [34][35][36]. Proposed underlying mechanisms fall into two camps: reflex theory and reflux theory [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that GERS may lead to or exacerbate asthma and be associated with poor asthma control [34][35][36]. Proposed underlying mechanisms fall into two camps: reflex theory and reflux theory [35].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed underlying mechanisms fall into two camps: reflex theory and reflux theory [35]. Reflex theory suggests that esophageal acid induces a vagally mediated reflex leading to bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causal link is unclear, co-existence of gastroesophageal reflux is very common in patients with asthma [89]. As the diagnosis of GERD may be difficult, with limited sensitivity of both gastric pH monitoring and endoscopy, a trial treatment with PPI may be used as the initial diagnostic step in symptomatic patients [90]. Of note, high use of beta 2 -agonist has been shown to relax the sphincter between the oesophagus and the ventricle, which increases the tendency to reflux, potentially inducing a vicious cycle of high SABA use, reflux and increasing asthma symptoms leading to high SABA use.…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…The effect of treating GERD in severe asthma is uncertain: Whereas some studies have demonstrated an effect on symptoms, quality of life and exacerbations, no convincing effect has been demonstrated on lung function and airway hyperresponsiveness [90,150]. Hence, PPI treatment may be considered in the individual patient.…”
Section: Management Of Severe Asthmamentioning
confidence: 99%